PENGARUH MOTIVASI KERJA TERHADAP KINERJA DOSEN PEREMPUAN PADA SEKOLAH TINGGI ILMU EKONOMI (STIE) DI KOTA PEKANBARU - Gultom, Elida (Eko dan Bisnis: Riau Economic and Business Review, 2018)
This study aims to determine the effect of work motivation on the performance of female lecturers at Sekolah Tinggi Ilmu Ekonomi (STIE) in Pekanbaru City.The total population is 126 people with a sample of 56 respondents. The method of collecting data using a questionnaire. The data analysis technique used is simple linear regression with SPSS 23 for Windows. Based on the results of the analysis obtained a simple linear equation Y = 4.333 + 0.196X. The results of the t-test hypothesis are obtained that, t count> t table (5.006> 2.004) with probability (0.00 <0.05). R-Square determination test results amounted to 0.317.The results showed that there was a significant effect of work motivation on the performance of female lecturers at Sekolah Tinggi Ilmu Ekonomi (STIE) in Pekanbaru City. The size of the contribution of work motivation variable (X) affects the variable performance of female lecturers (Y) by 31.7% and the remaining 68.3% is influenced by other variables not examined in this study